2023
DOI: 10.1111/ene.16023
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain does not detect self‐reported treatment‐related fluctuations in chronic inflammatory demyelinating polyneuropathy

Philip Lennart Poser,
Gulchan Shazadi Sajid,
Léon Beyer
et al.

Abstract: IntroductionSerum neurofilament light chain (sNfL) is a marker for axonal degeneration. Patients with CIDP often report a fluctuation of symptoms throughout one treatment cycle with immunoglobulin (IVIG). The aim of this study was to determine whether sNfL is suitable to quantify patient reported symptom fluctuations.Methods29 patients with the diagnosis of CIDP or a CIDP‐variant under treatment with IVIG were recruited in this study and underwent examination before IVIG infusion, in the middle of the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…An increase in serum NfL was confirmed to be associated with disease progression 1 year after serum sampling in patients with CIDP but has not been shown to reflect short-term treatment responses after IVIg administration. 3840 In our study, we also confirmed that serum NfL was not associated with treatment responsiveness to initial IVIg. Instead, the levels of serum glycans were associated with short-term initial response to IVIg treatment.…”
Section: Discussionsupporting
confidence: 81%
“…An increase in serum NfL was confirmed to be associated with disease progression 1 year after serum sampling in patients with CIDP but has not been shown to reflect short-term treatment responses after IVIg administration. 3840 In our study, we also confirmed that serum NfL was not associated with treatment responsiveness to initial IVIg. Instead, the levels of serum glycans were associated with short-term initial response to IVIg treatment.…”
Section: Discussionsupporting
confidence: 81%